HUBUNGAN SOSIAL BUDAYA DAN PERAN GURU DENGAN RENDAHNYA PELAKSANAAN PHBS DI SDN 001 LANGGINI KECAMATAN BANGKINANG KOTA - Rizki Rahmawati Lestari (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2018)
More and more diseases arise because of the difficulty of applying PHBS, including: abdominal pain such as diarrhea, dysentery, cholera, typhus, eye pain such as the causes of frequent bathing in dirty water, elephantiasis/filariasis, caused by mosquitoes spread by filaria, skin aches such as itching, phlegm, ringworm, ringworm, water lice, and intestinal worms. The purpose of this study was to determine the socio-cultural relations and the role of teachers with the low implementation of PHBS in SDN 001 Langgini Bangkinang Kota District in 2018. The quantitative research design was cross-sectional. The population in this sample amounted to 49 people. The sample in this study amounted to 49 people. The sample technique used is total sampling. The instrument used was a questionnaire. The data obtained were analyzed by the chi-square test, the significance level was 95%. The results of this study indicate that there is a significant relationship between socio-culture and PHBS Implementation in Schools P value 0.025 (pâ‰¤0.05), indicating a significant relationship between the role of teachers and the implementation of PHBS in schools P value 0.047 (pâ‰¤0.05. For SDN 001 Langgini District Bangkinang City can be taken into consideration in preparing policies relating to the problem of implementing PHBS and provide information to students to always apply PHBS at school